Claudius the god and his wife Messalina : the troublesome reign of Tiberius Claudius Caesar, Emperor of the Romans (born 10 B.C., died A.D. 54), as described by himself, also his murder at the hands of the notorious Agrippina (mother of the Emperor Nero) and his subsequent deification, as described by others - Graves, Robert, 1895-1985 (Penguin, 1954)
Based on the life of Claudius, Emperor of Rome.